Role of multi slice computed tomography in lung parenchymal pathologies - Bala, Neeshu; Ohri, Poonam; Guneet; Bhagat, Suman; Kohli, Manasi; Kohli, Parushi (International Journal of Research in Medical Sciences, 2025)
Background: Lung parenchymal pathologies cover a range of conditions such as interstitial lung diseases (ILD) bronchogenic carcinoma, pulmonary tuberculosis, aspergilloma, and many others. Multislice computed tomography (MSCT) has significantly aided in the diagnosis and management of lung parenchymal pathologies. Its high-resolution imaging capability and detailed cross-sectional view of the lungs help to detect and evaluate a wide range of pulmonary diseases with greater accuracy. Objective was to analyze the MSCT findings in patients with suspected lung parenchymal pathologies and assess its role in differential diagnosis and disease characterization. Methods: An observational cross-sectional study was performed in 100 patients with clinical suspicion of lung parenchymal pathologies. All patients underwent MSCT and imaging findings were correlated with clinical data wherever available. Results: The most common imaging features were consolidation (56%), cavitation (24%), ground-glass opacities (24%), fibrosis (23%). Infective pathologies accounted for the majority of findings, including consolidation, nodules, bronchiectasis, and cavitatory lesions. Neoplastic lesions were seen in 8% of cases, all showing advanced features such as lymphadenopathy and local invasion. Additional findings included pleural effusions (20%), pneumothorax (7%), and mediastinal involvement (58%). MSCT enabled accurate identification and characterization of various pathologies such as tuberculosis, bronchogenic carcinoma, ILD, aspergilloma, and allergic bronchopulmonary aspergillosis (ABPA). Conclusions: MSCT plays a vital role in the early detection, accurate characterization, and staging of lung parenchymal diseases. Its high diagnostic yield enhances clinical decision-making and guides appropriate management strategies.